Mercy Watson thinks like a pig - DiCamillo, Kate.; Van Dusen, Chris (Cambridge, MA : Candlewick Press, 2008)
Two sisters move in next door to where Mercy the pig lives, and frustrated when Mercy continues to eat their flowers decide to call for the help of an Animal Control Officer, Francine Poulet, to handle the case.
2.6
K-3
Keywords: Swine -- Juvenile fiction; Flowers -- Juvenile fiction; Pigs -- Fiction; Flowers -- Fiction; Humorous stories; Pigs -- Fiction; Flowers -- Fiction; Humorous fiction; Humorous stories